Sustainability of Rural Development Projects within the Working With People Model: Application to Aymara Women Communities in the Puno Region, Peru. - Sastre-Merino, Susana (2013)
Development projects have changed from a technical and top-down vision to an integrated view pursuing economic, social and environmental sustainability. In this context, planning and management models with bottom-up approaches arise, as the Working With People (WWP) model, that emphasizes on the participation and social learning, also incorporating a holistic approach stemming from its three types of component: ethical-social, technical-entrepreneurial and political-contextual. The model is applied in a rural development project, managed by an Aymara women’s organization in Puno, Peru. The WWP model is considered as a useful vehicle for promoting leadership and capacity building in technical, behavioral and contextual project management skills, so that women may become protagonists of their own development, thereby transforming their craft activities into successful and sustainable businesses.